Urban Agriculture in Latin America: A Green Culture Beyond Growing and Feeding - Castellarini, Fabiana (Frontiers in Sustainable Cities, 2022)
Over the coming decades, the level of urbanisation in Latin America (LA) is expected to increase nearly 90 percent, with unwanted consequences such as accentuated socio-economic inequalities, food insecurity, violence, and environmental and health crises. In LA countries, urban agriculture (UA) has been adopted as one of the major strategies to address urban poverty and food insecurity, which have increased for different drivers, such as population growth, economic crises, or forced migration. Nevertheless, experience in these countries has demostrated that urban agriculture is a complex activity that involving multiple benefits, risks, actors, processes, scales, and interactions. In this review, I analyse urban agriculture in LA countries using the ecosystems services framework as a tool to integrate UA functionalities and the four sustainability dimensions. I considered five issues deriving from plant production: (1) ecosystem services, benefits, assests, drivers and stakeholders in UA; (2) ecosystem services bundles; (3) economic and socio-cultural factors associated with the ecosystem services bundles; (4) research progress in LA countries; (5) issues and possible strategic directions in decision-making of UA in the LA region. Using proxy variables, a total of 17 ecosystem services, six benefits, six assets and six indirect drivers were recognized. Projections of the 17 variables over the four dimensions of sustainable development showed that the environmental dimension was most studied than the social, economic and governance dimensions. Most of strengths of UA in LA were related to ecosystem services, benefits, and beneficiaries; the main weaknesses were related to the misuse of inputs, and human and environmental health; threats were related to regulation, governance and land tenure issues, and opportunities to diverse topics related to the four dimensions of sustainability. The concepts, frameworks and methods used in this study may be effective tools to make scientific information available to managers and decision makers.